Nieswoista choroba zapalna jelit o wczesnym i bardzo wczesnym początku - Daniluk, Urszula; Kierkuś, Jarosław; Lebensztejn, Dariusz (Pediatria Polska - Polish Journal of Paediatrics, 2017)
It is known that certain patients with very early onset IBD (diagnosis before 6 years of age) have a higher possibility of immune deficiency with monogenetic aetiology. The growing prevalence of these types of disorders forces the gastroenterologist to gain some knowledge about the symptoms and further diagnostic management, which includes consultation with the clinical immunologist. The resemblance of the clinical manifestation of early-onset Crohn's disease with ulcerative colitis and high incidence rate of unclassified IBD suggests caution in IBD diagnosis in younger patients.